Chemical modulation of chemotherapy resistance in cultured oesophageal carcinoma cells. (February 2000) - Sheehan, D.; Meade, G.
Abstract : Oesophageal carcinoma is a common form of cancer in developing countries, especially in the Caspian littoral and northern China. In contrast, it has a much lower incidence in Japan, the U.S.A. and western Europe. Certainly in the case of squamous cell oesophageal carcinoma, dietary composition, smoking, alcohol and exposure to nitrosamines are major risk factors that may partly explain the disease's geographical distribution. The prognosis for oesophageal carcinoma is generally poor, due to the high incidence of distant metastasis and local recurrence. Combination treatment with both cisplatin and 5-fluorouracil is the most common chemotherapy regime used. We have carried out a detailed study of sensitivity of two oesophageal cell lines: OC1 cells from a squamous carcinoma of a male patient, and OC2, a squamous carcinoma obtained from a female patient. Both cell lines are sensitive to Vinca alkaloids and doxorubicin, while being quite resistant to alkylating agents such as cisplatin and l, 3-bis-(2-chloroethyl)-1-nitrosourea. This pattern of resistance suggests a possible role for glutathione S-transferase (GST) and/or glutathione (GSH) in resistance, and would seem to exclude the multidrug resistance phenotype. Both cell lines possess mainly Pi-class GSTs, and have distinct levels of GSH, with OC2 possessing some 25 % of the level of OC1 cells. Effects of a variety of modulating agents on the pattern of resistance, such as the GSH depleter, buthionine sulphoximine, and the GST inhibitor, ethacrynic acid, were determined. An unexpected observation was that ethacrynic acid appears to increase the level of GSH in both cell lines.